All-optical dual module platform for motility-based functional scrutiny of microencapsulated probiotic bacteria - Wang, Zhe; Giugliano, Giusy; Behal, Jaromir; Schiavo, Michela; Memmolo, Pasquale; Miccio, Lisa; Grilli, Simonetta; Nazzaro, Filomena; Ferraro, Pietro; Bianco, Vittorio (Biomedical optics express, 2024)
Probiotic bacteria are widely used in pharmaceutics to offer health benefits. Microencapsulation is used to deliver probiotics into the human body. Capsules in the stomach have to keep bacteria constrained until release occurs in the intestine. Once outside, bacteria must maintain enough motility to reach the intestine walls. Here, we develop a platform based on two label-free optical modules for rapidly screening and ranking probiotic candidates in the laboratory. Bio-speckle dynamics assay tests the microencapsulation effectiveness by simulating the gastrointestinal transit. Then, a digital holographic microscope 3D-tracks their motility profiles at a single element level to rank the strains.